2020
DOI: 10.5114/pedm.2020.93249
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and periodontal status in children with type 1 diabetes mellitus

Abstract: Dental caries and periodontal status in children with type 1 diabetes mellitus Intensywność próchnicy zębów oraz stan przyzębia u dzieci chorujących na cukrzycę typu 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 13 publications
0
21
0
3
Order By: Relevance
“…Regarding the influence of glycemic control elements on the presence of gingivitis, data are not conclusive, suggesting other factors, such as those related to patients' immunological responses (55). A recent study showed no significant differences in periodontal status between controlled and poorly controlled diabetic patients and healthy children (56). In a case-control study involving 80 children and adolescents (aged 5-18 years) with T1DM, a significant effect of diabetes on an increased risk of oral and periodontal diseases in children was not confirmed (57).…”
Section: Plaque-induced Gingivitis and T1dmmentioning
confidence: 99%
“…Regarding the influence of glycemic control elements on the presence of gingivitis, data are not conclusive, suggesting other factors, such as those related to patients' immunological responses (55). A recent study showed no significant differences in periodontal status between controlled and poorly controlled diabetic patients and healthy children (56). In a case-control study involving 80 children and adolescents (aged 5-18 years) with T1DM, a significant effect of diabetes on an increased risk of oral and periodontal diseases in children was not confirmed (57).…”
Section: Plaque-induced Gingivitis and T1dmmentioning
confidence: 99%
“…Діти з цукровим діабетом, незалежно від вираженості патологічного процесу в пародонті, повинні перебувати на обліку у лікарястоматолога. Лікувально-профілактичні заходи стоматологом слід проводити з урахуванням основного соматичного захворювання [10,11].…”
Section: вступunclassified
“…Наявність у дітей цукрового діабету І типу є основним фактором ризику виникнення запальних захворювань пародонту. Для дітей з даною ендокринною патологією характерні наступні особливості: вимушений частий прийом їжі (часто з метою попередження гіпоглікемії діти вживають вуглеводи швидкої дії у вигляді меду чи льодяників); порушення процесів самоочищення в порожнині рота; зменшення резистентності макроорганізму і локальних факторів захисту; порушення в системі орального гомеостазу, обумовлені змінами в регуляторній (інтегративній), секреторній, захисній, видільній, мінералізуючій і травній функції слинних залоз; акумуляція зубного нальоту; мінімальний рівень протиінфекційного захисту ротової порожнини; підви-щення активності анаеробної мікробної флори; систематичне транзитне оновлення агресивної мікрофлорою еко ніші ротової порожнини через коливання рівня глікованого гемоглобіну; гіпосалівація і т.д [4,6,10].…”
Section: вступunclassified
“…The early detection of at-risk youngsters could reduce the incidence of caries lesions per patient and the average cost for prevention and treatment. The number of studies trying to correlate salivary proteins and dental caries has considerably increased [ 7 , 24 , 26 , 27 , 28 , 29 , 30 ]. It has been reported that changes in salivary protein compositions are involved in dental caries etiology [ 26 , 29 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%